URBAN HEAT ISLANDS CHARACTERIZATION USING SENTINEL 3 SLSTR. A CASE STUDY IN MADRID (SPAIN, SEPTEMBER 2024) - Gómez-López J. M. (НТУ «ДП», 2024)
According to a World Bank report (2023), currently more than half of the world's population lives in urban areas, and the growth of these areas is expected to continue in the coming decades, especially in certain regions (Central and South America and Asia), so that by 2050 it is estimated that 7 out of 10 people will be living in urban areas. It is clear that these are areas with special problems, since they imply on the one hand a strong dynamism of change with very important contributions to the GDP (80% of GDP is linked to these areas), but also environmental alterations that must be taken into account, due to the consequences not only for the environment, but also for the quality of life and health of the people who live in them.